Essays on corporate bankruptcy reorganization and liquidation - Amaral, Gustavo Henrique de Oliveira (2022)
The recurring global and local economic crises have highlighted how crucial bankruptcy regimes are to the stability of the economic environment. Despite the relevance of corporate bankruptcy, there is scant empirical research on the topic in emerging market contexts. This doctoral dissertation addresses this void through three essays founded on the growing literature of empirical legal studies and evidence-based law. First, we survey empirical research on corporate bankruptcy through a systematic literature review. We provide an overview of the theoretical literature on the topic, propose a conceptual framework, and critically review the empirical literature, identifying a potential agenda for future research. Second, we investigate the spillover effects of bankruptcy reorganization and liquidation on corporate creditors. Based on a novel dataset on bankruptcy proceedings judicial data from the State Court of São Paulo (TJSP) matched to the Brazilian employer-employee administrative data (RAIS), we employ a difference-in-differences matching estimator strategy to compare the performance of bankrupt firms creditors (treated group) and similar firms without any business relationship with a bankrupt firm (control group). Our findings indicate that the contagion effects of bankruptcy reach both the treated group (corporate creditors) and control group (similar firms with no direct link to a bankruptcy reorganization event). There is little evidence that the impact is different between the two groups. Moreover, we assume that the adverse spillover effects on both groups are mainly from bankruptcy reorganization cases converted to liquidation. The third essay examines the effects of the bankruptcy law amendment by the complementary law LC 147/2014 on the distribution of creditors bargaining power in bankruptcy reorganizations. We argue that the partial split of unsecured creditors into a new class of only small-sized unsecured claimholders intended to give more power to this group in the negotiations of the restructuring plan. We consider the law reform as a source of variation, and we employ mean t-tests and model specifications to assess mean differences in firms performance. Data on the proposed plan (creditors haircuts and tenor for repayment) and the administrative employee dataset (number of employees) are used as proxies for performance to examine the effects on the small-sized claimants. The results indicate that the 2014 law reform produced small effects on the ex-ante bargaining practice in bankruptcy reorganizations. Debtors generally propose equal haircuts to both unsecured creditors and the new class of small-sized unsecured creditors. Despite the better terms for small-sized unsecured creditors regarding a shorter time for repayment, the economic significance is low because of an average payment tenor of ten years to the new class. The three essays reveal the importance of empirical legal studies to provide evidence and critical information for evaluating and assisting legal reforms, public policy debates, legal practitioners interpretations of the norms, and academic research.